IMPLICATIONS OF DIGITAL TRANSFORMATION IN THE WORKPLACE AND ITS IMPACT ON WORKPLACE HARASSMENT OR MOBBING SITUATIONS - Aguirre Espinosa, Juan Esteban (2024)
This research article analyzes the regulatory changes in the labor field in Colombia during the COVID-19 pandemic and their impact on preventing digital workplace harassment. The global health emergency has generated the creation of norms aimed at regulating new forms of work, such as telework and distance work. However, the use of information and communication technologies in remote work has increased the risk of digital workplace harassment, which has generated the need to adapt regulatory provisions to the new realities of work. This essay analyzes the contribution, contradiction, practice, and evaluation of digital evidence in workplace harassment processes, where evidence becomes a fundamental element for the accreditation of facts and the generation of corresponding legal effects.